Desenvolvimento de uma proposta pedagógica para o ensino da cinemática através da robótica educacional - LEITE, Dadson Luís Ferreira (2021)
The teaching of Physics in basic education has a series of problems identified by many researchers, ranging from the way these concepts are worked at this stage, through the lack of motivation of students and untrained professionals to teach Physics, until the lack of appropriate classroom and laboratory infrastructure for experimental practice. Associated with all these issues some students have mistaken conception about physics in high school when interpreting it as being contextualized mathematics. Despite these difficulties, many teachers believe in their role as facilitators and can lead their students’ learning through the tools and teaching that combine technology with education in order to motivate them to produce knowledge and awaken the interest of reaching more beyond. With this in mind, we developed a pedagogical proposal based on a didactic sequence that uses a robotic educational tool to facilitate the teaching of Kinematics for high school students. Such proposal incorporates the use of a robot developed to observe their trajectories in different circumstances of movement, in which the recording of movements takes place through graphics generated by an application for smartphone and tablet called Phyphox. The theoretical framework for learning this proposal is anchored in the perspective of the theory of constructivism and constructionism. The validation of our proposal and the verification of student learning takes place through classroom use of student interaction and participation and through the application of questionnaires. The set of these assessment instruments believes that our proposal can be used as a classroom practice to understand the concepts of Kinematics because as obtained from the collected data, they discriminate against a significant influence on the teaching-learning process.